Hubungan Dukungan Keluarga Dengan Proses Pemulihan Pasien Halusinasi - ninuk, devin; Widiatie, Wiwiek; Khasana, Faizatul (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
Hallucinations are one of the symptoms of mental disorders where patients experience changes in sensory perception, feeling false sensations in the form of sound, sight, taste, touch or inhalation. The recovery process of hallucination patients does not only depend on medical treatment therapy, but also requires support from the surrounding environment, especially family. This study aims to analyze the relationship b etween family support and the recovery process of hallucination patients at Puskesmas Dukuh Klopo, Peterongan District, Jombang Regency. This study used an observational analytic design of non-experimental research using a cross sectional approach. All families who have family members with hallucination disorders at Puskesmas Dukuh Klopo, Peterongan District, Jombang Regency as a population. Stratified Random Sampling technique which is divided into 6 villages with a total of 55 respondents. From the results of the study obtained respondents with good support as much as 63.6%, enough as much as 27.3%, less as much as 9.1%, while patients with a good recovery process as much as 70.9%, enough as much as 29%, and less as much as 0%. The results of the statistical analysis of the Spearman's rho correlation test with a significance level of α = 0.05 showed a ρ value of 0.000. The correlation coefficient value of 0.505 means that there is a moderate relationship and shows that the hypothesis is accepted, so there is a relationship between family support and the recovery process of hallucination patients. This study shows that family support is a significant factor in the recovery process of hallucination patients ABSTRAK Halusinasi adalah salah satu gejala gangguan jiwa dimana pasien mengalami perubahan sensori persepsi, merasakan sensasi palsu berupa suara, penglihatan, pengecap, perabaan atau penghirupan. Proses pemulihan pasien halusinasi tidak hanya bergantung pada terapi pengobatan medis, melainkan juga membutuhkan dukungan dari lingkungan sekitar, terutama keluarga. Penelitian ini bertujuan untuk menganalisis hubungan dukungan keluarga dengan proses pemulihan pasien halusinasi di Puskesmas Dukuh Klopo Kecamatan Peterongan Kabupaten Jombang. Penelitian ini menggunakan desain analitik observasional penelitian non eksperimen dengan menggunakan pendekatan cross sectional. Seluruh keluarga yang mempunyai aggota keluarga dengan gangguan halusinasi di Puskesmas Dukuh Klopo Kecamatan Peterongan Kabupaten Jombang sebagai populasi. Teknik Stratified Random Sampling yang terbagi dalam 6 desa dengan jumlah responden sebanyak 55 responden.Hasil penelitian didapatkan responden dengan dukungan baik sebanyak 63,6%, cukup sebanyak 27,3%, kurang sebanyak 9,1%, sedangkan pasien dengan proses pemulihan baik sebanyak 70,9%, cukup sebanyak 29%, dan kurang sebanyak 0%. Hasil analisis statistik uji korelasi Spearman’s rho dengan taraf signifikansi α = 0,05 menunjukkan ρ value sebesar 0,000. Nilai koefisien korelasi 0,505 artinya ada hubungan sedang dan menunjukkan hipotesa diterima, jadi ada hubungan antara dukungan keluarga dengan proses pemulihan pasien halusinasi. Penelitian ini menunjukkan bahwa pentingnya peran keluarga dalam proses pemulihan pasien halusinasi.